2020
DOI: 10.3390/molecules25092052
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Amidodithiophosphonato Nickel(II) Complexes: An Experimental and Theoretical Approach

Abstract: The reactions of 2,4-bis(4-methoxyphenyl)-1,3-dithio-2,4-diphosphetane-2,4-disulfide (Lawesson’s Reagent, LR) with benzylamine (BzNH2) and 4-phenylbutylamine (PhBuNH2) yield benzylammonium P-(4-methoxyphenyl)-N-benzyl-amidodithiophosphonate (BzNH3)(BzNH-adtp) and 4-phenylbutylammonium P-(4-methoxyphenyl)-N-(4-phenylbutyl)-amidodithiophosphonate (PhBuNH3)(PhBuNH-adtp). The relevant nickel complexes [Ni(BzNH-adtp)2] and [Ni(PhBuNH-adtp)2] and the corresponding hydrolysed derivatives (BzNH3)2[Ni(dtp)2] and (PhBuN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The analysis was based on an in-vitro evaluation by using a study design previously described in the literature and reported in the CLSI (Clinical Laboratory Standards Institute) and in the EUCAST (European Committee for Antimicrobial Susceptibility Testing) [15][16][17] (Figure 1). biofilm formation.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was based on an in-vitro evaluation by using a study design previously described in the literature and reported in the CLSI (Clinical Laboratory Standards Institute) and in the EUCAST (European Committee for Antimicrobial Susceptibility Testing) [15][16][17] (Figure 1). biofilm formation.…”
Section: Methodsmentioning
confidence: 99%
“…Standard drugs (a set of commercial antibiotics and antimycotics) were used for a comparative evaluation with our compounds [ 63 , 64 ]. The primary data are available in the supplementary materials session [ 65 , 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the class of amidodithiophosphonato (ligand IV in Scheme 1) metal complexes remains still unexplored, possibly due to their tendency to hydrolysis at P─N bonds. [19][20][21] In this respect, we have been developing a synthetic program based on the ability of neutral dithiophosphonato and dithiophosphato Ni II complexes to assemble CPs in combination with a variety of polypyridyl donors, in particular 4,4'-bipyridine and its analogues. [22,23] It was demonstrated that the primary structural motif of these polymers mainly depends on the features of the spacers such as length, rigidity and orientation of the donor atoms, as recently confirmed by the deliberate stereospecific generation of homochiral polymeric helices built from a designed enantiopure binaphthyl-based ligand.…”
Section: Introductionmentioning
confidence: 99%